Dataset from : Browsing is a strong filter for savanna tree seedlings in their first growing season - Archibald, Sally; Twine, Wayne; Mthabini, Craddock; Stevens, Nicola (ARCHIBALD ECOLOGY LAB, 2021)
1: Newly germinated seedlings are vulnerable to biomass removal but usually have at least six months to grow before they are exposed to dry-season fires, a major disturbance in savannas. In contrast, plants are exposed to browsers from the time they germinate, making browsing potentially a very powerful bottleneck for establishing seedlings. 2: Here we assess the resilience of seedlings of 10 savanna tree species to top-kill during the first 6 months of growth. Newly-germinated seeds from four dominant African genera from across the rainfall gradient were planted in a common garden experiment at the Wits Rural Facility and clipped at 1 cm when they were ~2, 3, 4, and 5 months old. Survival, growth, and key plant traits were monitored for the following 2.5 years. 3: Seedlings from environments with high herbivory pressure survived top-kill at a younger age than those from low-herbivore environments, and more palatable genera had higher herbivore-tolerance. Most individuals that survived were able to recover lost biomass within 12 months, but the clipping treatment affected root mass fraction and branching patterns. 4: Synthesis: The impact of early browsing as a demographic bottleneck can be predicted by integrating information on the probability of being browsed and the probability of surviving a browse event. Establishment limitation through early-browsing is an under-recognised constraint on savanna tree species distributions. Data may be used without requesting permission after the J Ecology paper is published and in the public domain (estimated after October 2021).
Seedlings
Description: The paper is prepublication, details of the paper will be added once published. Sally Archibald: sally.archibald@wits.ac.za. Centre for African Ecology, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, Private Bag X3,WITS, 2050, South Africa.
Keywords: browse-trap; demographic bottlenecks; distribution limit; tolerance; survival; seedling establishment; resprouting; herbivory; savanna tree species; consequences of global climate change; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Plant and forest protection